MENJADI TIONGHOA YANG BUKAN KAFIR: KAJIAN ATAS KONSTRUKSI IDENTITAS TIONGHOA MUSLIM DI PALEMBANG - Herwansyah Herwansyah (Jurnal Studi Agama, 2019)
So far, studies on Chinese Muslims has been carried out in Java, but on the contrary, has not been studied extensively outside Java. Having a Muslim and Chinese identity at the same time is not easy, it is due to the stereotype that Malay (read Islam) and Chinese are different, while Malay is Islam, whereas Chinese is not Islam. This study used documentations, in-depth interviews and observations. The documentations include literature studies concerning history of Chinese Muslims in Palembang. Meanwhile, interviews, observations are used to capture the phenomena that occur today. Finally, this study use the the notion that identity is a social construction. The construction of Chinese Muslim identity in Palembang was achieved through several factors, among others (1) related to the social structure behind it, (2) memories of the past (Halbwachs, 1980), (3) consumption culture (Storey, 1999), (4) adjustment to tradition (Hobsbawn, 1983) and (5) imagined through mass media (Anderson, (1991)